Similar efficacy and tolerability of raltegravir-based antiretroviral therapy in HIV-infected patients, irrespective of age group, burden of comorbidities and concomitant medication: Real-life analysis of the German 'WIP' cohort. (August 2017) - Naumann, U; Moll, A; Schleehauf, D; Lutz, T; Schmidt, W; Jaeger, H; Funke, B; Witte, V
Only limited efficacy and tolerability data on raltegravir (RAL) use are currently available. Study objectives were to describe the efficacy and tolerability profile of RAL-based antiretroviral therapy (ART) in routine clinical practice in Germany. The WIP study (WIP = "Wirksamkeit von Isentress unter Praxisbedingungen", Efficacy of Isentress under routine clinical conditions) was a prospective, multi-centre cohort study in Germany. Human immunodeficiency virus (HIV)-infected patients aged ≥ 18 years in whom combinational ART with RAL 400 mg BID was indicated were enrolled. The primary endpoint was virologic response (HIV-RNA <50 copies/mL; non-completion equals failure) after 48 weeks. Of 451 patients, 85.1% (n = 384) were still receiving RAL at week 48. At baseline (BL), the prevalence of concomitant diseases was higher in patients of the age group ≥50 years (94.2% vs. 75.7%) as well as concomitant medications (74.8 % vs. 55.4%). Virologic response at week 48 was 74.7% (overall), 75.0% (naïve at BL), 81.5% (suppressed at BL), 47.1% (interrupted previous treatment at BL) and 64.9% (failing at BL), without significant differences by age group. A significant correlation of achievement of HIV-RNA <50 copies/mL was seen with treatment status at BL (p = 0.004). In addition, 77.3 % of the patients with a CD4 cell count >200 cells/µL at BL achieved HIV-RNA <50 copies/mL (p = 0.029). RAL was well tolerated with 80 adverse events (AEs) in 49 patients (10.9%) and 8 serious AEs (SAEs) in 6 patients (1.3%) reported to be drug related. A total of 22 patients (4.9%) discontinued treatment due to AEs. The WIP study shows that the previously reported efficacy and safety profile of RAL can be achieved in a population with multiple comorbidities and comedications, with no major difference observed in ageing patients (≥50 years) vs. younger patients. RAL is therefore an attractive treatment option in routine medical care in Germany.